Analytical Thinking Abilities in Physics Education Students: A Rasch-Based Diagnostic Study - Amsor Amsor; M Reza Dwi Saputra; Nurdini Nurdini; Filzah Nabila Asri; Siti Almaidah (Postgraduate, University of Mataram, 2025)
Analytical thinking is essential for physics education students, yet comprehensive assessment remains challenging. This study investigates the distribution and characteristics of analytical thinking abilities using Rasch model analysis, examining gender differences and performance patterns. A cross-sectional study was conducted with 35 physics education students (20 females, 15 males) using a 20-item multiple-choice assessment covering four domains: identifying problems, recognizing relational patterns, identifying reasoning errors, and summarizing main ideas. Data were analyzed using Winsteps software to examine person abilities and group comparisons. Results revealed highly variable analytical thinking abilities (range = 8.84 logits, M = -0.15, SD = 1.79). Males outperformed females by 0.46 logits (males: M = 0.15; females: M = -0.31), though not statistically significant (p > 0.05). Three performance levels emerged: high achievers (25.7%, n = 9), average achievers (48.6%, n = 17), and low achievers (25.7%, n = 9). The findings reveal significant heterogeneity in analytical thinking abilities with observable gender-based differences. Results suggest the need for differentiated instructional approaches tailored to varying ability levels and targeted interventions to support struggling students. This study demonstrates the utility of Rasch analysis in identifying areas for instructional improvement and optimizing analytical thinking development in physics education contexts